Switching of delta opioid receptor subtypes in central amygdala microcircuits is associated with anxiety states in pain - Zhou, Wenjie (J Biol Chem, 2021)
Anxiety is often comorbid with pain. Delta opioid receptors (DORs) are promising targets for the treatment of pain and mental disorders with little addictive potential. However, their roles in anxiety symptoms at different stages of pain are unclear. In the current study, mice with inflammatory pain at the fourth hour following complete Freund’s adjuvant (CFA) injection displayed significant anxiety-like behavior, which disappeared at the seventh day. Combining electrophysiology, optogenetics, and pharmacology, we found that activation of delta opioid receptor 1 (DOR1) in the central nucleus amygdala (CeA) inhibited both the anxiolytic excitatory input from the basolateral amygdala (BLA) and the anxiogenic excitatory input from the parabrachial nucleus (PBN). In contrast, activation of delta opioid receptor 2 (DOR2) did not affect CeA excitatory synaptic transmission in normal and 4-h CFA mice but inhibited the excitatory projection from the PBN rather than the BLA in 7-day CFA mice. Furthermore, the function of both DOR1 and DOR2 was downregulated to the point of not being detectable in the CeA of mice at the 21st day following CFA injection. Taken together, these results suggest that functional switching of DOR1 and DOR2 is associated with anxiety states at different stages of pain via modulating the activity of specific pathways (BLA-CeA and PBN-CeA).